IMPROVEMENT OF THERMOREGULETORY INDICES OF LACTATING BUNAJI, WADARA AND FRIESIAN X BUNAJI COWS FED DIETARY ORGANIC ANTI-OXIDANT UNDER TROPICAL ENVIRONMENT - Adamu, S.; Bishir, B. B.; Gbor, V.; Ibrahim, Y.; Adamu, N.; Umar, Y. P. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
The study was conducted at the dairy research and development centre of Abubakar Tafawa Balewa University, Bauchi to evaluate the effects of baobab fruit pulp meal supplementations as organic anti-oxidants on improvement of thermoregulatory indices of Bunaji, Wadara and Friesian x Bunaji cows fed dietary organic anti-oxidant under tropical environment. Twenty (24) lactating cows in their first and second parity were used. They were allotted to four dietary levels (0.00, 5.30, 10.60 and 15.90 kg/100 kg diet of BFPM) with six animals per treatment in a Completely Randomized Design (CRD). The data generated was subjected to analyses of variance of SPSS software and the means were separated using Tukey Pairwise Comparison method. Friesian x Bunaji cows had higher (P ≤ 0.05) respiratory rate, rectal temperature, pulse rate and skin temperature compared to Wadara and Bunaji breeds. Second parity had higher respiratory rate, pulse rate and skin temperature compared to first parity. Lactating cows fed diet supplemented with baobab fruit pulp meal at level 15.90 kg/100 kg had higher (P≤ 0.05) thermoregulatory values while the cows fed control diet had lower values. In conclusion, the inclusion of baobab fruit pulp meal at 15.90 kg/100 kg had reduced heat stress (rectal temperature) by reducing thermoregulatory indices in dams. It is recommended that, under tropical conditions baobab fruit pulp meal as organic anti-oxidants and constituent of glutathione peroxidase could be added at 15.90 kg/100 kg in the diet of lactating cows for improved body physiological processes and reduction of negative effects of thermoregulatory stress indices without any deleterious effect.